Biodiversity and climate change adaptation in tropical islands - Sivaperuman, C. (Chandrakasan); Velmurugan, A.; Singh, A. K.; Jaisankar, I. (Academic Press, 2018)
'Biodiversity and Climate Change Adaptation in Tropical Islands' provides comprehensive information on climate change, biodiversity, possible impacts, adaptation measures and policy challenges to help users rehabilitate and preserve the natural resources of tropical islands. While biodiversity and climate change of tropical islands has previously received less attention, it is ironically one of the most vulnerable regions in this regard. The core content of the work derives largely from the ideas and research output from various reputed scientists and experts who have recorded climate change impacts on aquatic and coastal life in tropical regions. Contributors have direct working experience with the tribes in some of the tropical islands. All of their expertise and information is compiled and presented in the work, including coverage related to climate change. This work highlights the ever-growing need to develop and apply strategies that optimize the use of natural resources, both on land and in water and judicious use of biodiversity. It functions as a critical resource on tropical island biodiversity for researchers, academicians, practitioners and policy makers in a variety of related disciplines. --